The Trial of Socrates. Ethical and Legal Issues - IUGA, Nicolae (Journal of Legal Studies, 2014)
In contemporary researches on Ethics, the study subject of this discipline seems to be simple and is considered as being a sociological, given fact. From this perspective, the subject of Ethics is provided by the external experience, the observation of the social world and of the rules of conduct, including the ones pertaining to certain professional fields, which are actually followed or just proclaimed verbally, as well as by the internal experience, our own sense regarding the idea of good and acceptance of the moral rules. However, this way of perceiving things has an important shortcoming: it cannot explain an ethical conduct which is defining for the human being, the heroic conduct. There are people with strong characters who, in the name of some ethical ideals, make choices that do not pursue personal interests. On the contrary, the choices can prejudice them greatly and even putting their own lives in danger. We are talking about choices that are not conditioned internally or externally, neither socially or by personal emotions, but are ethical imperatives that refer to unconditional and unrelated values, to the definite and absolute. Our present endeavor seeks to highlight how the manifestation of the Unconditional occurs in the case of exemplary ethical personality of antiquity and how the Unconditional reveals itself as being a divine imperative, a metaphysical principle.